Pengaruh Green accounting, Kinerja Lingkungan, dan Pertumbuhan Penjualan Terhadap Profitabilitas - Suci Mahdani Hardi; Emma Saur Nauli Sipayung (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine the effect of Green accounting, Environmental Performance, and Sales Growth on Profitability. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) using secondary data obtained from annual and sustainability reports during the 2021-2023 period. The amount of data in this study was 306 observations. The data was analyzed using Eviews12 with the panel data regression method. The results showed that simultaneously Green accounting, Environmental Performance, and Sales Growth have an influence on Company Profitability. Partially, Sales Growth has a positive effect on Profitability, while Green accounting and Environmental Performance have no positive effect on Profitability.